Analisis Trend Ekspor Teh Indonesia - Andi, Yusrizal Ari; Baroh, Istis; Ibrahim, Jabal Tarik (University of Muhammadiyah Malang, 2019)
Tea is one of Indonesia's leading plantation commodities exported to the international market. Indonesia itself is the sixth largest exporter of tea in the world. The Indonesian tea market tends to decline and impact on the decline of tea export. The decline in Indonesian tea exports is due to many factors. This study aims to (1) Analyze the trend of Indonesian tea exports and (2) Analyze what factors may affect Indonesian tea exports. The data used in this study is secondary data in the form of time series data (time series data) from 2006-2015. The analysis method used is trend analysis method and continued by ordinary least square method (OLS). The results of this research are (1) the trend of Indonesian tea export is declining because the amount of tea export volume keeps decreasing and the export value of tea also decreases and does not increase. (2) volume of Indonesian tea production (), domestic prices (), export prices (), the rupiah exchange rate against the dollar () simultaneously affect the export of Indonesian tea (Y). while the factors that affect Indonesian tea exports individually and the most influential are export prices (), and the rupiah exchange rate against the dollar ().